Modeling Relationships of Affective Factors on Grade Eight Students’ Mathematics Achievement - Dr. Muhammad Akhtar Kang; Dr. Ahmad Saeed, (Dialogue Social Science Review (DSSR), 2025)
The current study employed a quantitative research design to explore the intricate network of affective factors linked with academic achievement in mathematics among 8th-grade students in Karachi. A total of 160 students (80 boys and 80 girls) were selected from ten randomly selected private schools. The study reviewed the contemporary literature highlighting the paramount role of affective traits for academic success in mathematics and presented the multi-dimensional relations among motivation, attitude, belief, academic engagement, and academic achievement. With the help of structural equation modeling, the study assessed the direct and indirect relationships of factors affecting achievement, thereby revealing the underlying complexity within the framework of a theoretical model. The results show a significant relationship of students’ self-beliefs with their motivations, engagement, and achievement in mathematics. The study also explored the moderating role of belief about the teacher in the relationship between affective variables and mathematics achievement, thereby emphasizing the importance of the teacher-student positive relationship in enhancing mathematics achievement. The findings have implications for the creation of supportive learning environments that foster mathematics achievement as well as for the development of evidence-based interventions that may enhance mathematics education in urban schools in Karachi.